Frequency of Abnormal CT Scans and the Correlation with Patients Complaints in Emergency Department - Khosroshahi, Nahideh; Khayatzadeh-Kakhki, Simin; Alehossein, Seyedmehdi; Eftekhari, Kambiz (Iranian Journal of Child Neurology, 2025)
Objectives Computed tomography (CT) scans are one of pediatric emergency departments’ most informative and widely used techniques. The research aimed to investigate the frequency of abnormal brain CT scan and determine its correlation with patient complaints in the emergency department. Materials & Methods A retrospective review was conducted on the records of children who presented with various neurological complaints at the Bahrami Children’s Hospital, a referral hospital in Tehran, Iran, over a five-year period (2016-2020). The study included patients who had undergone an emergency brain CT scan within the first 24 hours of their consultation. Results Two hundred eligible children, with a mean age of 5.47±3.81 years, were included in this study. They were categorized into seven groups according to their chief complaints. Based on the findings, 113 patients (58.5%) had normal CT scan reports. The remaining CT scan findings, in order of frequency, included imaging results related to the primary diagnosis (19%), incidental findings (12%), and indications of preexisting disorders (10.5%). Seizure was the most common complaint, leading to a brain CT scan (34%). Children presenting with focal neurological symptoms accounted for the highest frequency of CT scan abnormalities. Conclusion This study concluded that most children presenting with neurological complaints have either normal or insignificant findings on their brain CT scans. Given the potentially harmful effects of radiation exposure, as well as considerations of healthcare costs and time, it is essential to adhere to precise protocols when conducting these scans.